OSMOTIC RESPONSE OF TIGER SHRIMP (Penaeus monodon) BROOD STOCK IN VARIOUS MOLTING STAGES - Sutrisno Anggoro; Agung Setiarto (JOURNAL OF COASTAL DEVELOPMENT, 1998)
The attempt to optimize shrimp culture production has faced with several problems related to its biotechnical management, which was suspected unable to meet the needs of the cultured species. This is primary because the ecophysiological characteristics of shrimp, particularly those related to the osmoregulation mechanism in connection with their growth, have not been sufficiently understood. The research was aimed at studying the ecophysiological characteristics of tiger shrimp (Penaeus monodon) involved in biotechnical management of shrimp hatchery with special emphasis on the osmotic response and isosmotic medium requirement for adult spawners in various molting stages. The results showed that osmotic responses were closely realted to the salinity of water medium and molting phases. It was also found that the minimum osmotic works of tiger shrimp occurred in isosmotic medium, i.e. 34 – 35 ppt for premolt, 33 – 34 ppt for molt and 30 – 31 ppt for intermolt stages.